Peningkatan Keterampilan Berpikir Tingkat Tinggi (Higher Order Thinking Skills) pada Siswa Sekolah Dasar Melalui Video berbasis Kasus Pencemaran Lingkungan - Zajuli Ichsan, Ilmi; Iriani, Enin; Muthi Hermawati, Farah (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2018)
Learning Natural Sciences on environmental pollution material is one of the important topics. Students at the elementary school level have an important role in protecting the environment around them. This research was conducted with the aim of increasing the Higher Order Thinking Skills (HOTS) of students in science learning in the environmental material. The research method used in this study is Classroom Action Research with details of 3 cycles. The study was conducted during October 2018 at SDN Jatimulya 02, Bekasi. The number of samples taken was 35 students. The treatment given is by playing case-based learning videos in the classroom. The results showed that there was an increase in HOTS students in science learning using case-based videos. The conclusion is that case-based learning videos can increase HOTS students of SDN Jatimulya 02.